Conversion between basic density and apparent density at any moisture content in Eucalyptus grandis - Costa, Vladimir Eliodoro [UNESP]; Rezende, Marcos Antonio de [UNESP]; Rodrigues, Valdemir Antonio [UNESP] (Walter De Gruyter Gmbh, 2014)
Wood basic density (BD) is related to other wood characteristics and its determination is important in forest inventory, though BD must be differentiated from the apparent density (AD), which relates to the moisture content (MC) of wood. The aim of this study is to demonstrate a reliable conversion from BD to AD for any MC of Eucalyptus grandis wood based on two exponential and linear models that relate volumetric shrinkage to MC. To this end, wood specimens were submitted to drying and the volumetric shrinkage was determined as a function of MC. The two models proved to be efficient in the conversion of BD to AD and vice versa.
Keywords: apparent density; basic density; density conversion; Eucalyptus grandis; specific gravity; wood